2019
DOI: 10.1089/jwh.2018.7163
|View full text |Cite
|
Sign up to set email alerts
|

Developing Physician Educational Competencies for the Management of Female Genital Cutting: A Call to Action

Abstract: Female genital cutting (FGC), also called female genital mutilation, is defined as ''all procedures involving partial or total removal of the external female genitalia or other injury to the female genital organs whether for cultural, religious, or other nontherapeutic reasons.'' FGC can have significant health consequences, including multiple physical and psychological complications, throughout the life course. Despite violating numerous human rights and existing legal prohibitions, the practice continues. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…All of the people interviewed reported a lack of training in FGM, both in their academic education and after joining the workforce. This reality is shared with other countries where there is a significant number of people from at-risk countries [20,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…All of the people interviewed reported a lack of training in FGM, both in their academic education and after joining the workforce. This reality is shared with other countries where there is a significant number of people from at-risk countries [20,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…As Atkinson and Geisler (2019) have pointed out, "Education and training about FGC should be incorporated into American medical education programs, both at undergraduate and graduate levels, as well as offered as part of continuing medical education initiatives : : : " (p. 3). The findings of this study highlight a knowledge gap that extends outside the medical profession.…”
Section: Trainingmentioning
confidence: 99%
“…Finally, it is important to note that while numerous gaps in the field have been identified and acknowledged in the U.S.—ranging from the need for advocacy to the need for educational competencies and culturally informed practices (Atkinson et al, 2019; Atkinson & Geisler, 2019; Nour, 2015)—the main focus of the few studies conducted regarding health care professionals has been on the perspectives and practices of medical professionals in the U.S. (Hess et al, 2010; Lane et al, 2019; Moaddab et al, 2017). Until recently, the experiences of other professionals have been largely ignored (Akinsulure-Smith & Sicalides, 2016).…”
Section: Fgc Researchmentioning
confidence: 99%
“…Data extrapolated from 2004 to 2008 East African regional surveys of girls and women 15 years and older revealed that 82% to 99% reported to have had undergone FGM/C, and of these cases, 34% to 79% were type III (Somalia having the highest prevalence of type III). [29][30][31][32] One recent US study revealed that of 79 general pediatricians surveyed, 73% had received no previous FGM/C education, 89% did not feel confident in their ability to identify FGM/C types, and frequency of performing external genital examinations on female patients at health supervision visits was inversely related to the age of the patient (with 75% performing examinations on infants, down to only 8% in 17-to 18-year-olds). 28 In literature from other high-income countries with immigrant populations from regions where FGM/C is prevalent, pediatricians have reported identifying FGM/C in pediatric patients, managing complications from remote and recent procedures, and, in some instances, being asked to perform FGM/C in children.…”
Section: Fgm/c Types and Classificationmentioning
confidence: 99%